Análisis de las características de las incubadoras de empresas en Colombia: un estudio de casos ﻿ - Peña-Vinces, Jesús C. (2011)
Based on the research methodology of case study, in this article we analyze the main characteristics that condition business’s survival of four business’s incubators in Colombia (Bucaramanga, Créame, ParqueSoft and Gestando). The researchers applied the guide of best practices of the business’s incubators of Nodriza as a tool for the exploratory analysis. The results reveal that 70% of the companies comply with this guide, allowing them to continue surviving at the domestic and international market.